2013
DOI: 10.1080/09593330.2013.770561
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organochlorine pollutants and metals residues in sediment and freshwater fish species cultured in a shallow lagoon, Egypt

Abstract: Six freshwater fish species cultured in Lake Edku fish farm, one of the northern Nile Delta lakes in Egypt that receives input from numerous anthropogenic activities in addition to agriculture wastes through several huge drains, were collected for the detection and evaluation of residues of the persistent organochlorine (OC) pollutants polychlorinated biphenyls (PCBs), 1,1,1 -trichloro-2,2-di(4-chlorophenyl)ethane (DDT), total cyclodienes (TC), hexachlorocyclohexanes (HCHs) and heavy metals (Cu, Cd and Pb) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Because they are usually highly persistent as well as lipophilic, organochlorines tend to accumulate in the fat deposits of animals, especially those with poor metabolic and excretory capabilities for these pollutants, such as marine mammals [114]. In a study conducted in Egypt on the concentration of PCBs (as one of EDCs) in muscle tissues of some cultured freshwater fish, which represent the main meal of fish for the vast majority of Egyptians people, it was found that the concentration ranges from (1.646-22.768 ng/g).This result indicates that agricultural activities (as the fish farm feed on mixed wastes) have affected the water quality of in which the fish live; these organic contaminants are transported to the people through the diet causing a lot of troubles [97].…”
Section: Occurrence Of Edcs In Marine Organismsmentioning
confidence: 91%
See 1 more Smart Citation
“…Because they are usually highly persistent as well as lipophilic, organochlorines tend to accumulate in the fat deposits of animals, especially those with poor metabolic and excretory capabilities for these pollutants, such as marine mammals [114]. In a study conducted in Egypt on the concentration of PCBs (as one of EDCs) in muscle tissues of some cultured freshwater fish, which represent the main meal of fish for the vast majority of Egyptians people, it was found that the concentration ranges from (1.646-22.768 ng/g).This result indicates that agricultural activities (as the fish farm feed on mixed wastes) have affected the water quality of in which the fish live; these organic contaminants are transported to the people through the diet causing a lot of troubles [97].…”
Section: Occurrence Of Edcs In Marine Organismsmentioning
confidence: 91%
“…These smallest aquatic organisms are eaten by successively larger, predator fish which are then consumed by fish-eating mammals. The PCBs in surface sediments of Egyptian Mediterranean coast are predominant over all kinds of pesticides the concentration was ranged from 0.31 to 1.95 ng/g [97].…”
Section: Occurance Of Edcs In Aquatic Environmentmentioning
confidence: 99%
“…In a study conducted in Egypt on the concentration of PCBs (as one of EDCs) in muscle tissues of some cultured freshwater fish, which represent the main meal of fish for the vast majority of Egyptians people, it was found that the concentration ranges from (1.646-22.768 ng/g).This result indicates that agricultural activities (as the fish farm feed on mixed wastes) have affected the water quality of in which the fish live; these organic contaminants are transported to the people through the diet causing a lot of troubles [97].…”
Section: Occurrence Of Edcs In Marine Organismsmentioning
confidence: 91%
“…The previous studies in Lake Edku were dealing with physical and chemical characteristics (Shakweer, 2006;Badr and Hussein, 2010;Abdel Halim et al, 2013;Khalil and Rifaat, 2013). Persistent organochlorine pollutants, metals residues in sediment, water, freshwater fish species and aquatic macrophytes were also investigated (Badr and Fawzy, 2008;Barakat et al, 2011;Shreadah et al, 2012;Abdallah and Morsy, 2013). Unfortunately, foraminiferal data in Lake Edku was very few (e.g., Samir, 2000).…”
Section: Introductionmentioning
confidence: 99%